Protest and Culture. Concepts and Approaches in Social Movement Research - Ullrich, Peter; Daphi, Priska; Baumgarten, B. (Conceptualizing Culture in Social Movement Research, 2014)
Social movements have been very present lately, both in public discourse and the media as well as in scholarly research: Occupy Wall Street, the Arab Spring, and the Indignados protests have kept observers on their toes. Why do these movements emerge? How do they evolve over time? And what explains their resonance within society at large? Culture plays a prominent role in answering these questions: It heavily influences the emergence, existence, and development of our ‘movement society’. The central purpose of this edited volume is to provide a conceptual systematisation of the current state of cultural approaches in research on social movements and protest, a niche that is yet to be filled on the book market. Going beyond a collection of existing approaches, it particularly addresses facets of cultural theory that so far have been largely neglected in literature on social movements.